Demand forecast for road transportation fuels including gasoline, diesel, LPG, bioethanol and biodiesel for Turkey between 2013 and 2023 - Melikoğlu, Mehmet (Pergamon-Elsevier Science Ltd, 2014)
In Turkey, more than 90% of passengers and goods are transported by roads. In order to flow this immense traffic nearly 2.7 million m(3) of gasoline, 11.5 million m(3) of diesel, and 5.2 million m(3) of liquefied petroleum gas (LPG) was consumed in 2011. Starting from 2013, Turkey plans to blend biofuels to gasoline and diesel gradually reaching to 10% (volume) by 2020. Turkey's economy has been growing at unprecedented rates since 2003. As a result, both diesel and LPG consumption reached to record levels. Yet, gasoline demand decreased almost linearly in the same period. Accordingly, forecasting road transportation fuel demand becomes more difficult and yet more important than ever before. Gasoline, diesel, LPG, bioethanol and biodiesel demand has been forecast for the first time in this study using semi-empirical models in the view of Turkey's Vision 2023 goals, Energy Market Regulatory Authority targets, and European Union directives. The models suggested that in 2023, annual gasoline consumption in Turkey could decrease below 2.0 million m(3), whereas, diesel and LPG consumption could rise to 16.4 and 8.8 million m(3), respectively. Consequently, 0.3 million m(3) of bioethanol and 1.4 million m(3) biodiesel could be required to fulfil the official targets in 2023. (C) 2013 Elsevier Ltd. All rights reserved.
Keywords: Biodiesel; Bioethanol; Demand forecasting; Diesel; Gasoline; LPG